SOCIALLY RESPONSIBLE INVESTING AS THE DI-RECTION OF CAPITAL MARKET DEVELOPMENT - Grażyna Michalczuk; Urszula Konarzewska (Polityki Europejskie, Finanse i Marketing)
Socially responsible investing (SRI) is becoming an increasingly fast-growing segment of the capital market. It refers to transactions in which the investment objective is determined not only by financial criteria (expected rate of return and risk) but also by non-financial aspects related to environmental, social and corporate governance (ESG) issues.The aim of the article is to diagnose socially responsible investing in the capital markets in spatial terms. An additional aim is to identify the strategies implemented by investors in individual markets.The classical methods of research were used in this article, such as the study of the literature concerning socially responsible investing and the method of desk research based on documents showing global trends in socially responsible investing in terms of value and investment strategies used by investors.Referring to statistics, it can be seen that socially responsible investing becomes a significant form of locating funds in a global capital market. In 2020, the global value of the SRI market amounted to over USD 35 trillion. However, it is not a homogeneous market, as evidenced by thevarying rates of development of socially responsible investing in different regions of the world. It is also a market that evolves in terms of the investment strategies used. This is reflected in moving away from making investment decisions mainly with the use of negative/exclusionary screening toinvestments made on the basis of ESG integration.